Critique of Afghanistan's Criminal Judicial Policy on Criminal Influence - Motahari, Dr. Sayed Ali (International journal of multicultural and multireligious understanding, 2025)
Criminal abuse of influence; in addition to disrupting the rule of law and governance, is one of the complex and serious problems of Afghanistan's judicial system and an obstacle to criminal justice. While the administration of criminal justice and the rule of law are considered the most important issues of governance and the judicial and legal system, this article, using a descriptive-analytical method and relying on library and documentary sources, attempts to answer this question: What deficiencies does Afghanistan's judicial-criminal policy face in dealing with criminal abuse of influence? Although this behavior is criminalized under the title of 'abuse of influence' in Afghanistan's Penal Code, findings from examining various dimensions of judicial-criminal policy in dealing with this phenomenon show that legal gaps, weak independence of the judiciary, inefficiency of oversight institutions, lack of coordination between judicial and legal institutions; non-compliance with fundamental criminal principles and sentencing standards, susceptibility of courts and judges to influence, and interference and influence by individuals throughout the judicial process are considered the most significant challenges in the judicial and legal system. The aforementioned deficiencies have led to increased corruption and public distrust in the judicial system, weakened the rule of law and judicial institutions, as well as caused the spread of judicial deviation and social disorder. Measures such as legislative reform and the development of comprehensive and clear laws regarding the crime of abuse of influence, specialized training for judges and staff of judicial and investigative institutions, implementation of measures to reduce political interference and ensure judicial independence, strengthening independent oversight institutions and increasing transparency, establishing effective mechanisms for cooperation between judicial and legal institutions to reform and strengthen judicial-criminal policy regarding criminal abuse of influence; are proposed.